A place preference test in the fish Nile tilapia - Delicio, Helton Carlos [UNESP]; Barreto, Rodrigo Egydio [UNESP]; Normandes, Edvaldo Bento [UNESP]; Luchiari, Ana Carolina [UNESP]; Marcondes, Ana Lúcia [UNESP] (Elsevier, 2006)
The Nile tilapia fish (Oreochromis niloticus) has a high potential to be used as a model in neuroscience studies. In the present study, the preference of the Nile tilapia between a gravel-enriched (GEE), a shelter-enriched (SEE) or a non-enriched (NEE) environment was determined, for developing a place preference model. Nile tilapia had an initial preference for GEE, but after 1 day of observation, the fish stabilized their frequency of visits among compartments. Hence, any stimulus motivating tilapia increase in compartment visiting indicates a positively reinforcing effect. This feature is very useful for the development of new behavioural paradigms for fish in tests using environmental discrimination, such as the conditioning place preference test. © 2006 Elsevier GmbH. All rights reserved.
Keywords: Behaviour; Conditioning place preference; Fish; Nile tilapia; Oreochromis niloticus; animal behavior; animal experiment; animal housing; aquatic environment; behavioral science; controlled study; decision making; experimental animal; female; male; motivation; nonhuman; observational study; place preference; reinforcement; Tilapia; visual discrimination; visual stimulation